Test and characterisation of STS/MuCh-XYTER and integration with multiple detectors of CBM-MuCh detector systems. (1st January 2023) - Saini, J.; Ghosh, C.; Dubey, A.K.; Ahammed, Z.; Mondal, M.; Ganai, R.; Sikder, G.; Negi, V.; Chattopadhyay, S.; Chakrabarti, A.; ,
Abstract: Compressed Baryonic Matter (CBM) is a fixed target experiment at the upcoming Facility for Anti-proton and Ion Research in Germany, having collision rates up to 10 MHz. Due to the proximity of the target and secondaries produced in absorbers, Muon Chambers (MuCh) of the CBM experiment will face a very high particle hit rate of up to 400 kHz/cm 2 in its first two stations. To cope with these particle rates, a Gas Electron Multiplier (GEM) detector will be used for the first two stations while, due to relatively lower particle rates, the last two stations will use a low resistivity Bakelite Resistive Plate Chamber (RPC) detector. The electronics of these two MuCh detectors need different dynamic ranges. A Silicon Tracking Station (STS) system made of 300 μm thick silicon micro-strip sensors will be installed upstream of the MuCh detector system. The sensors will be read out through multi-line micro-cables with fast electronics. The micro-strip sensors will be double-sided with a stereo angle of 7.5°, a strip width of 58 μm, and strip lengths between 20 and 120 mm requiring high-density readout. To meet the high rate and high density requirements of MuCh and STS, respectively, a specialized 128-channel readout ASIC with a dual-gain feature is designed. This is a highly configurable ASIC with about 30, 000 configurable register bits which control various bias and threshold settings of the ASIC. To integrate this ASIC with both the detector systems, detailed testing and characterization of the ASIC are required. Due to the high number of configurable registers and several operating conditions, characterizing this ASIC is very challenging. This paper describes the optimization procedures of several configurable bias parameters in detail and also explains how this ASIC is integrated with both GEM and RPC detectors of the MuCh system.